Examining change in entrepreneurial networks: Using visualisation as an alternative approach. Issue 2 (April 2019) - Soetanto, Danny
Abstract: Although network-based research in entrepreneurship has considered the importance of networks for small firm growth, studies have been criticised for their contradictory inferences on how entrepreneurs should embed in networks, and for overlooking the fact that networks are dynamic in nature. In this paper, we seek to contribute to entrepreneurial network literature by exploring changes in entrepreneurial networks using a network mapping approach. To meet our research objectives, we implement an innovative research design (network mapping) where entrepreneurs visually demonstrate how their networks have changed. We find that entrepreneurial networks evolve dynamically in relation to entrepreneurial stages such as opportunity exploration, initial resource gathering, incubation, early market entry, and growth. Based on the characteristics of network, the change can be defined as the initial networks change towards support-based networks, market-based networks, and the development of core networks. Given the nature of these findings, this study contributes to fostering understanding on network changes and the effectiveness of a network mapping approach as an alternative data collection methodology in network research.